Pathways to internationalization in agronomy: institutional strategies and challenges from a regional perspective - Barroso Leyva, Marienny; Pazmiño Calero, Lucy Marina; Basantes Arias, Elsa Amalia (Dominio de las Ciencias, 2025)
The internationalization of higher education has become a critical component in preparing professionals for a globalized world. This article explores the pathways adopted by a regional public university in Ecuador to internationalize its Agronomy degree program. Through an institutional analysis, the study identifies key strategies including the integration of foreign language instruction, cross-border academic cooperation, and the alignment of curricular components with international standards. Despite structural and geographic limitations, the program has made progress in embedding internationalization through academic flexibility, student engagement in collaborative projects, and initiatives to strengthen digital and intercultural competencies. The article highlights the importance of coordinated institutional planning, external partnerships, and responsive policy frameworks in advancing internationalization in regional contexts. The findings contribute to a broader understanding of how agricultural education can evolve to meet global challenges while remaining rooted in local realities.